Effect of free nitrous acid on nitritation process: Microbial community, inhibitory kinetics, and functional biomarker. (March 2023) - Liu, Yucan; Zhu, Yuliang; Wu, Daishun; Wang, Zhaoyang; Wang, Yajun; Wang, Gang; Zhou, Xin; Sun, Hongwei
Graphical abstract: Highlights: AOB population was enriched through long-term inhibition of FA on NOB activity. FNA-dependent response of the biological nitritation process was investigated. Hellinga model could perfectly describe the nitritation inhibition by FNA. FNA reduced the Nitrosomonas abundance, but increased the Paracoccus abundance. Nitrosomonas was the key biomarker indicating the nitritation to FNA constraint. Abstract: This work comprehensively deciphered the effect of free nitrous acid (FNA) on the microbial community, inhibitory kinetics, and nitrifiers in nitritation process. Nitritation was first successfully achieved through selective inhibition of free ammonia (FA) on nitrite oxidizers (NOB). Then, batch tests clearly showed that FNA significantly inhibits the ammonia oxidation rate ( r su ) and the growth rate ( μ ) of ammonia oxidizers (AOB), which was well described by the Hellinga model ( K I  = 0.222 mg·L −1 ). The structural equation model indicated that FNA was significantly and negatively associated with r su, μ, Nitrosomonas, Commamons, Nitrospira, and Nitrotoga and positively correlated with Paracoccus . Furthermore, Nitrosomonas significantly drove the ammonia utilization and growth of AOB and was identified as the most important functional biomarker indicating the nitritation in response to FNA levels using random forest model. This study provides helpful information on the kinetics of the mechanism underlying the FNA inhibition on nitrification.